ASSOCIATION BETWEEN MODE OF DELIVERY AND BREASTFEEDING PRACTICES: A PROSPECTIVE STUDY IN A TERTIARY CARE HOSPITAL - FATIMA , SS; SULTAN , S (Biological and Clinical Sciences Research Journal, 2024)
Breastfeeding is widely recognised to have numerous health benefits for the infant and child health later, such as lowering the risk of gastrointestinal tract infections, respiratory tract infections, allergies, asthma, obesity, type I and type 2 diabetes mellitus (DM), and sudden infant mortality syndrome. It also protects mothers against conditions like obesity, type 2 DM, and breast and ovarian cancers. Objective: To assess the association between mode of delivery and breastfeeding practices. Methodology: This cross-sectional study was carried out in the obstetrics department of Lady Reading Hospital after approval from the hospital’s ethical committee. The study duration was three months, from 1st November 2023 to 31st January 2024. Postnatal mothers were interviewed, and information was collected on a specifically designed proforma 24 hours after the birth of the baby and then on the day of discharge from the hospital. Using openepi software, keeping anticipated frequency 18%, confidence level 95%, power of study 80%, sample size calculated is 227. Data was entered into SPSS version 20. Results: In the current study, 227 patients were enrolled. Based on age-wise distribution, 125 (55.07%) patients were 16-25 years old, 67 (29.52%) were 26-35 years old, and 35 (15.42%) patients were more than 35 years of age. Amongst 227 women, 109 (48.02%) delivered vaginally while caesarean section was done in 118 (51.98%) patients. Based on the initiation of breastfeeding, amongst 109 women who delivered vaginally, breastfeeding within one hour was initiated in 79 (72.48%) patients. In comparison, amongst 118 women with caesarean section within one hour, breastfeeding initiation was observed in 74 (62.71%) patients. The association between breastfeeding initiation and mode of delivery was statistically significant (p=0.001). Conclusion: Our study concludes that the chance of delayed breastfeeding initiation was higher in women who had caesarean delivery. Hence, Counseling regarding the initiation and maintenance of breastfeeding should be a mandatory part of prenatal care provided to women by hospitals. Adequate professional support must be available in the postnatal wards, especially for women who delivered by cesarean section, and should be tailored according to the individual needs.